A Design for a Randomized Controlled Trial to Assess the Effect of Clinical Audits on Ambulatory Care in Hospital Clinics - Baines, Johanna Cornelia (My University, 1980)
A design is presented for a randomized controlled trial to answer the question: do audit procedures which hospitals are expected to carry out to meet requirements for hospital accreditation have a beneficial impact on ambulatory patient care in general and special clinics?
Approximately 60 Ontario hospitals reporting general and special ambulatory care clinics to Statistics Canada will be invited to participate in the trial. Outpatient visits to potentially eligible clinics will be documented by hospital medical records staff and submitted to the Hospital Medical Records Institute. Nurse abstractors will identify indicator conditions from this outpatient census and categorically score patient management over three periods of time: a pre-audit period before intervention occurs, a first audit period and a second audit period.
Hospitals stratified according to size and function will have been randomly allocated to three groups. Indicator conditions relevant to caseloads and casemix will be assigned to eligible clinics.
Groups I and II will both have indicator conditions introduced to clinic staff prior to the first audit period. Only Group I will receive feedback about their performance in the first audit period.
After the second audit period it should be possible to separate the effects of audit awareness (Groups I and II), of feedback (Group I) and of extraneous factors (Group III) on patient management. Results will be expressed as mean clinic scores.
If improved performances occur in Groups I and II, the usefulness of current accreditation criteria will have been demonstrated. If no change in performance occurs and the indicator condition criteria approach is accepted as being valid in this setting, then it may be appropriate to consider new approaches to accreditation.
Keywords: Medical Sciences; Medical Sciences